On Adjusting Vector Symbol Decoding for Many Different Nonbinary Convolutional Codes - Tuntoolavest, Usana; Chaiwan, Chanothai (Agriculture and Natural Resources, 2012)
The use of nonbinary convolutional codes with Vector Symbol Decoding (VSD) was proposed to correct long burst errors in high data rate wireless networks. VSD allows the symbol size to easily and arbitrarily increase as desired. Therefore, the same technique can be used for both the current data rate and any upcoming data rate of new wireless network standards. Convolutional VSD is more attractive than block VSD due to its lower complexity. Tables of convolutional codes with rate 2/3 and 3/4 are explicitly shown in the feedforward forms as required by VSD. The decoding performance was analyzed for several codes in an additive white Gaussian noise (AWGN) and a Rayleigh fading channel. The performance of VSD for different levels of decoder complexity was also tested. From the results, three design options that provide good performance were discussed including their advantages and disadvantages in terms of ﬂ exibility, complexity and ease of implementation.